Flame retardant composition for wood and wood-based materials using a compound of high concentration of boron and phenolic resin, flame retardant wood or wood-based material using the same, and method for producing the same
A high-concentration flame retardant composition of boric acid, sodium borate, and phenolic resin addresses the flammability and moisture sensitivity of wood materials, enhancing adhesion, moisture resistance, and dimensional stability while providing effective flame retardancy.
Patent Information
- Application Number
- JP2024556637
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-24
- Filing Date
- 2023-03-23
- Publication Date
- 2025-04-14
- Estimated Expiration
- 2043-03-23
AI Technical Summary
Wood materials are prone to flammability and moisture sensitivity, leading to adhesion issues and dimensional instability, especially when treated with boron-based flame retardants which have low solubility and high leachability.
A flame retardant composition comprising a high concentration of boric acid, sodium borate, and a water-soluble phenolic resin, which improves adhesion and moisture resistance while maintaining dimensional stability and enhancing flame retardancy.
The composition achieves significant improvements in flame retardancy, adhesion, and moisture resistance, allowing for the use of boron-based agents at higher concentrations without leaching, thereby stabilizing wood materials effectively.
Smart Images

Figure 2025510227000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a flame retardant composition for wood and wood-based materials, and flame retardant wood and wood-based materials using the same. More specifically, the present invention relates to a flame retardant composition for wood and wood-based materials comprising inorganic chemicals such as high-concentration boron compounds, i.e., boric acid and sodium borate, and a phenolic resin, and a method for producing flame retardant wood or wood-based materials using the same, which improves the reduced adhesive strength and moisture-vulnerable properties caused by inorganic treatment. [Background technology]
[0002] Wood is an environmentally friendly, human-friendly, and sustainable material, and has been used widely from prehistoric times to the present for various household items, furniture, and wooden buildings, and has a close relationship with humans. Furthermore, with the recent progress of global warming, wood, which is said to be a can of carbon dioxide, has once again come into the spotlight, and the use of wooden buildings that can be used for a long period of time is being recommended. However, such wood has the disadvantage of being easily rotten and flammable. In order to compensate for these disadvantages, and particularly to give fire resistance to wood, various researches on flame retardancy are being conducted.
[0003] Boric acid and sodium borate have been widely used for fire retardant treatment of wood, paper and wood-based materials, wood preservatives, termite control, etc. since Gay-Lussac discovered their fire resistance in 1823. In the 1970s, a mixture of boric acid, borax and inorganic salts was used by the US AWPA under the names of Minalith and Pyresote, and was also introduced early on in Korean university textbooks (Lee et al., 1981). However, so far, boron-based agents have been used at low content of 8% (wt%) or less due to their low solubility (Song et al. (2013), Jeong et al. (2018), Republic of Korea Patent 10-2015-012482), and have only been used as auxiliary agents for fire retardants (Lee et al. (1981), Wood Engineering, Hyangmun Co., Ltd., Song Dong-won et al. (2013): 3% each of boric acid and borax, Development of manufacturing technology for environmentally friendly fire-retardant wood. Research Reports of the Institute of Forest Science 13-20, Jeong Yong-jin et al.: Fire Sci. Eng., Vol. 32, No. 2, pp. 1-6, 2018: 4%) (Korea Patent No. 10-2015-0124482: 0.4-1 wt% boric acid, 1-5 wt% sodium borate; Korea Patent No. 10-2021-0064800: 0.6-0.7 wt% boric acid, 0.1-1 wt% borax).
[0004] The main reasons for this are, first, that the solubility in water at room temperature is low (boric acid 4.72 g, borax 4.71 g, 20°C); second, when the temperature is raised to perform high-temperature dissolution treatment to increase the solubility, precipitated crystals are formed on the wood surface, which hinders penetration and causes contamination of the wood surface due to efflorescence (for example, solubility at 80°C: boric acid 23.6 g, borax 44.3 g); third, when treated wood comes into contact with water, the leaching (exudation) of the chemicals becomes extremely high; and fourth, it is known that treatment of wood with boric acid or sodium borate hinders the formation of bonds, resulting in a decrease in strength, not only between identical materials but also between dissimilar materials (Laks et al. 1990). Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention has been developed to solve the above problems, and the object of the present invention is to provide a high-concentration phenol-boron-based flame retardant composition for wood, which compensates for the drawback of wood being vulnerable to fire, maintains a clean surface condition even after treatment, and imparts dimensional stability and flame retardancy without leaching out due to water, and to provide a flame-retardant wood using the same and a manufacturing method for the same. [Means for solving the problem]
[0006] The flame retardant composition for wood and wood-based materials according to the present invention is characterized by containing boric acid, sodium borate, and a water-soluble phenolic resin.
[0007] The composition contains, on a solid content basis, 16 to 36 wt% of the phenol resin, 8 to 18 wt% of boric acid, 10 to 22 wt% of sodium borate, and 18 to 40 wt% of boric acid-sodium borate. Hereinafter, the contents of the components are based on the solid content.
[0008] The phenolic resin is a liquid resol type produced by adding phenol, formalin, and water to a resin reactor, adjusting the pH to 10.7 to 11.0 with sodium hydroxide (NaOH), and reacting them.
[0009] The phenolic resin is a liquid resol type prepared by adding the phenol and the formalin to the resin reactor in a molar ratio of phenol:formalin (35%) = 1:1.63 to 2.4, adjusting the pH to 10.7 to 11.0 with sodium hydroxide (NaOH), and reacting at 70°C to 80°C.
[0010] The composition further contains resorcinol or bisphenol, which is a liquid resol type that can be co-condensed with phenol to produce a resin.
[0011] The resorcinol is contained in an amount ranging from 10 to 40 wt %.
[0012] The composition is also characterized in that it contains 23 to 33 wt% of resorcinol and 15 to 21 wt% of phenol resin, with the result that the resorcinol-phenol resin is in the range of 38 to 54 wt%, and 6.8 to 10.9 wt% of boric acid and 8.5 to 13.7 wt% of sodium borate, with the result that the boric acid-sodium borate is in the range of 15.3 to 24.6 wt%.
[0013] In addition, the boric acid and sodium borate are mixed to produce a boric acid-sodium borate mixture, and the boric acid-sodium borate mixture is characterized in that 25.53 wt% of boric acid and 31.91 wt% of sodium borate (borax) are added to water as a boric acid-sodium borate solution, the temperature is raised to 90°C to 100°C, and a transparent boric acid-sodium borate mixture that is highly soluble in water is produced, and the mixture is mixed with a phenolic resin to cause a reaction.
[0014] The method for producing a flame-retardant wood or a flame-retardant wood material according to the present invention further comprises the steps of: S1) preparing wood or wood-based material; S2) preparing a wood flame retardant comprising a mixture of phenolic resin, boric acid and sodium borate; S3) injecting the wood flame retardant comprising the phenolic resin-boric acid-sodium borate compound obtained in step S2) into the wood or wood-based material; and S4) drying and hardening the impregnated wood or wood-based material; The present invention is characterized by comprising:
[0015] Moreover, the step S2) includes the steps of: S2-1) producing a phenolic resin; S2-2) mixing boric acid and sodium borate in a solvent to produce a boric acid-sodium borate mixture; and S2-3) mixing and reacting the boric acid-sodium borate mixture with the phenolic resin.
[0016] The method further includes a step of carrying out a heat pressing process according to the wood material to manufacture a final wood material.
[0017] The wood or wood-based materials are characterized in that they are veneers, boards, particles, strands, and fibers obtained from logs, as well as plywood, laminated veneer lumber (LVL), laminated timber, structural cross-laminated timber (CLT), particle board, strand board, and fiberboard made from these.
[0018] In addition, in the step S2-1) of producing a phenolic resin, 94 g (1 mole) of phenol, 139.5 to 205.7 g (1.63 to 2.4 moles) of 35% formalin, and 14 to 20 g of water are charged into a resin reactor, the pH is adjusted to 10.7 to 11.0 with sodium hydroxide (NaOH), and the reaction is carried out at 70°C to 80°C to obtain a liquid resol type.
[0019] In addition, in the above step S2-2), boric acid and sodium borate are put into water and heated to 90°C to 100°C to produce a mixture of boric acid-sodium borate that dissolves well in water until it becomes transparent, and then in step S2-3), the above produced phenolic resin is mixed with 16-36 wt% phenolic resin, 8-18 wt% boric acid, 10-22 wt% sodium borate, and 18-40 wt% boric acid-sodium borate to cause a reaction.
[0020] In addition, in the step S2), after producing a compound of phenolic resin, boric acid and sodium borate, resorcinol is added to the compound of phenolic resin, boric acid and sodium borate to produce a flame retardant for wood.
[0021] In the above step S3), the injection method is characterized by diffusion and penetration at normal pressure.
[0022] In the above step S3), the injection method is a pressurization / depressurization method, and the main pressure is 10 to 25 kg / cm 2 The method is characterized in that the treatment is carried out at 0.5 to 120 minutes.
[0023] In the above step S3), pre-exhaust is performed for 30 minutes and post-exhaust is performed for 10 to 30 minutes before and after the main pressurization.
[0024] The method is also characterized in that it includes a step of stabilizing the wood or wood material injected in step S4) at room temperature, drying the wood or wood material at 50 to 70°C for a certain period of time, and then hardening the resin at 100 to 150°C.
[0025] Also, in step S5), the veneer is manufactured as plywood or laminated veneer lumber (LVL), the board is manufactured as laminated timber or structural cross-laminated timber (CLT), the particles are manufactured as particleboard, the strands are manufactured as strandboard, and the fibers are manufactured as fiberboard.
[0026] According to the flame retardant composition of the present invention as described above, an inorganic agent is used, but the phenolic resin improves the adhesive strength reduction and moisture vulnerability caused by inorganic treatment, and the reaction compound of a high-concentration mixture of boric acid-sodium borate and a phenolic resin provides a flame retardant composition for wood that can be stored for up to 2 months at room temperature (25 to 30°C). Furthermore, when the inorganic agent of boric acid-sodium borate is used as a fireproofing agent, it can be used as a main agent (fireproof adhesive) at a high concentration of up to 40%, unlike the conventional method in which it is used as an auxiliary agent at a composition of 8% (Wt%) or less. Therefore, a flame retardant consisting of a reaction compound of a mixture of boric acid-sodium borate with a high concentration composition and a phenolic resin can be an adhesive that maximizes the fire resistance of wood. Effect of the Invention
[0027] According to the present invention, a flame retardant composition for wood, which improves the deterioration of adhesive strength and the moisture-sensitive properties, is less susceptible to leaching due to water, has high dimensional stability, and has improved flame retardancy, and a method for producing the same are provided. [Brief description of the drawings]
[0028] [Figure 1] Fig. 1 is a photograph showing wood that has been flame-retardant treated in an embodiment of the present invention. The wood pattern is as clear as that of untreated wood. [Diagram 2] FIG. 2 is a photograph comparing untreated and flame-retardant treated boards before and after a leaching test (KS M 1701). [Diagram 3] Figure 3 is a photograph comparing untreated particleboard and flame-retardant treated particleboard before and after a leaching test (KS M 1701-2018). In the leaching test of the untreated particleboard, as shown on the right of 1, the thickness swelling rate was 48%, indicating a large expansion in thickness, whereas the flame-retardant treated particleboard (right of 2) showed a thickness swelling rate of 12%, indicating very high dimensional stability. [Figure 4]4 is a diagram showing the surface state of wood that has been flame retardant-treated in an embodiment of the present invention, as a result of an ignition test using a cone calorimeter. It can be seen that a carbonized layer is formed on the surface due to high temperature, but the back side is in a clean condition. [Diagram 5] FIG. 5 is a flow chart showing the steps of producing the flame-retardant wood or wood material according to the present invention. [Figure 6] 6 to 14 are graphs showing the results of the total heat release rate (THR) and heat release rate (HRR) in a performance test using a cone calorimeter in accordance with KS F ISO 5660-1 for wood that has been flame-retardant treated in the examples of the present invention. Both of the results meet the flame-retardant grade or higher. [Figure 7] Same as above [Figure 8] Same as above [Figure 9] Same as above [Figure 10] Same as above [Figure 11] Same as above [Figure 12] Same as above [Figure 13] Same as above [Figure 14] Same as above DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] The present invention will be described in detail below. Note that the terms used in the present specification and claims are not limited to their dictionary meanings or ordinary meanings, but should be interpreted as meanings appropriate to the technical content of the present invention.
[0030] The flame retardant composition for wood and wood-based materials according to the present invention contains boric acid, sodium borate, a water-soluble phenolic resin, and water.
[0031] The flame retardant composition contains 16 to 36 wt% of phenolic resin (solid content), 8 to 18 wt% of boric acid (solid content), 10 to 22 wt% of sodium borate (solid content), and 18 to 40 wt% of boric acid-sodium borate (total solid content).
[0032] The phenolic resin is a liquid resol type, and the flame retardant composition according to the present invention may further include resorcinol or bisphenol. Resorcinol or bisphenol is a liquid resol type that can be used to prepare a co-condensation resin with phenol.
[0033] The resorcinol in the flame retardant composition may be 10 to 40 wt %.
[0034] The flame retardant composition may contain 23 to 33 wt% of resorcinol resin (solid content) and 15 to 21 wt% of phenol resin (solid content), with the result that the resorcinol-phenol resin (total solid content) is in the range of 38 to 54 wt%, and 6.8 to 10.9 wt% of boric acid (solid content) and 8.5 to 13.7 wt% of sodium borate (solid content), with the result that the boric acid-sodium borate (total solid content) is in the range of 15.3 to 24.6 wt%.
[0035] Boric acid and sodium borate are mixed to produce a boric acid-sodium borate mixture. The boric acid-sodium borate mixture may be prepared, for example, by adding 25.53 wt % of boric acid and 31.91 wt % of sodium borate (borax) to water as a boric acid-sodium borate solution and heating the solution to 90°C to 100°C to produce a transparent boric acid-sodium borate mixture that is highly soluble in water, which may then be mixed with a phenolic resin to cause a reaction.
[0036] The method for producing the flame retardant composition for wood and wood materials of the present invention is described in detail below. The flame retardant agent comprising the flame retardant composition for wood and wood materials of the present invention is produced through three steps: a step of producing a phenolic resin, a step of mixing boric acid and sodium borate in a solvent to produce a mixture of boric acid and sodium borate, and a step of mixing the mixture of boric acid and sodium borate with a phenolic resin and reacting them.
[0037] In producing phenolic resin, phenol, formalin, and distilled water are charged into a reactor at room temperature, the pH is adjusted, and the mixture is reacted at a predetermined temperature for a predetermined time to produce a resol-type phenolic resin.
[0038] Phenol and formalin are charged into a resin reactor at a molar ratio of phenol:formalin = 1:1.63-2.4. In one specific example, 94g (1 mole) of phenol, 139.5-205.7g (1.63-2.4 moles) of formalin (35%), and 14-20g of distilled water are charged into the reactor at room temperature, the pH is adjusted to 10.7-11 with NaOH, and the reaction is carried out at a temperature of 70-80°C for 1 hour, whereby a resol-type phenolic resin (resin solid content: 51-53.4%, pH: 10.7-10.98, viscosity: 32-38.4 cps) is obtained as an intermediate product at a very high pH, low temperature, and short reaction time.
[0039] Moreover, phenol derivatives such as resorcinol and bisphenol may be used in place of phenol, and may be mixed with phenol to produce a resorcinol-phenol co-condensation resin.
[0040] In the step of producing the boric acid-sodium borate mixture, boric acid and sodium borate (borax) are added and heated to a predetermined temperature to produce a boric acid-sodium borate mixture that dissolves well in water until it becomes transparent.
[0041] In one specific example, a boric acid-sodium borate solution is produced by adding 25.53 wt% boric acid and 31.91 wt% sodium borate (borax) to water (42.56 wt%) and heating it to 90°C to 100°C until the mixture becomes transparent and soluble in water.
[0042] In the step of mixing and reacting the mixture of boric acid-sodium borate with the phenol resin, the mixture of boric acid-sodium borate prepared as described above is mixed with the phenol resin and reacted.
[0043] In this embodiment, the phenolic resin produced above is mixed with the following ingredients while maintaining the temperature at 60°C: phenolic resin solid content 16-36 wt%, boric acid solid content 8-18 wt%, sodium borate solid content 10-22 wt%, and total boric acid-sodium borate solid content 18-40 wt%, and reacted for 2 hours to obtain a water-resistant flame retardant composition for wood. This can be stored in liquid form at a temperature of 20-30°C for up to 2 months.
[0044] Furthermore, it is also possible to produce a flame retardant composition consisting of a water-resistant resorcinol-phenolic resin-boric acid-sodium borate mixture by adding 10 to 40 wt % of resorcinol while maintaining the mixture of phenolic resin-boric acid-sodium borate produced as described above at 60°C, reacting for an additional 2 hours, and storing the mixture at a temperature of 20 to 30°C.
[0045] The mixture of phenol-resorcinol resin·boric acid-sodium borate or the mixture of resorcinol-phenol resin·boric acid-sodium borate thus produced has a low solid content of phenolic resin and a low solid content of resorcinol resin, and if the total of the solid content of phenolic resin and the solid content of resorcinol is 30wt% or less, it is a case where the emphasis is placed on flame retardant treatment rather than adhesiveness for the flame retardant effect and dimensional stability of the flame retardant treated product, and if the total of the solid content of phenolic resin and the solid content of resorcinol is 40wt% or more, it has adhesiveness as the main effect and the flame retardant effect is obtained secondarily, so it is possible to add a hardener and a filler and perform cold or hot pressing like a normal adhesive used in the manufacture of plywood or laminated lumber. In this case, since it is used like a normal adhesive used for wood materials, the process is simple, unlike the complicated process of injecting a flame retardant. In the manufacture of plywood or laminated lumber, a part of the liquid flame retardant composition spreads to the wood part of the adjacent boundary surface just before the glue line is formed, and the adhesive layer itself forms a flame retardant layer, so that the more adhesive layers there are, the more flame retardant layers there are, and plywood with more flame retardant layers is more advantageous than laminated lumber. Therefore, the more flame retardant adhesive layers there are in the flame retardant plywood, the longer the fire resistance will be. As a result, when such flame retardant plywood is contained inside CLT, which is used as a structural material as well as plywood, it can fully play the role of a fire-resistant structure so that the structure will have fire resistance for a certain period of time or more depending on the application or components in the event of a fire.
[0046] Further, the flame-retardant wood or wood material according to the present invention and the manufacturing method thereof will be described below. Fig. 5 is a flow chart showing the manufacturing process of the flame-retardant wood or wood material according to the present invention.
[0047] The method for producing flame-retardant wood or wood material according to the present invention includes the steps of: S1) preparing wood or wood material; S2) producing a flame retardant for wood consisting of a compound of phenolic resin, boric acid and sodium borate; S3) injecting the flame retardant for wood consisting of a compound of phenolic resin, boric acid and sodium borate obtained in step S2) into the wood or wood material; and S4) drying and curing the injected wood or wood material.
[0048] Step S2) also includes the steps of producing a phenolic resin, mixing boric acid and sodium borate in a solvent to produce a boric acid-sodium borate mixture, and mixing and reacting the boric acid-sodium borate mixture with the phenolic resin.
[0049] Also, the method may further include a step of carrying out a heat pressing process depending on the wood material (particles, fiber, veneer, board) in S5) to manufacture a final wood material.
[0050] In the method for producing flame retardant wood and flame retardant wood materials according to the present invention, first, wood or wood materials are prepared. Wood is classified into various wood materials depending on the method of use. Wood can be sawn into boards or lumber, shaved or milled into thin boards, i.e., veneers, or ground or crushed into particles or fibers. These wood materials (particles, fiber, veneer, boards) are used to make wood-based materials, and they are manufactured as wood materials such as particleboard for particles, fiberboard for fibers, OSB for strands, plywood or laminated veneer lumber (LVL) for veneers, laminated lumber (glue-laminated timber, glulam) or cross laminated timber (CLT) for structures, and so on, and flame retardants are applied according to the process (mixing, injection, painting, covering).
[0051] Next, in the step of preparing a flame retardant, the above-mentioned flame retardant composition for wood and wood-based materials is produced.
[0052] Next, in the step of injecting the compound of phenolic resin, boric acid and sodium borate into the wood and wood-based materials, the injection method may include a method of diffusing and penetrating at room temperature, a pressurizing method, and a method of performing both evacuation and pressurizing treatment depending on the wood material and its thickness.
[0053] The boards are pressed at 10 to 25 kg / cm depending on the species. 2 or by using the vacuum / pressurization method, pre-evacuation (0.08MPa) for 30 minutes and pressure of 15-25kg / cm 2 The pressure is 10 to 25 kgf / cm for one hour, followed by 10 to 30 minutes of post-exhaust (0.08 MPa). The temperature is generally between room temperature and 60°C. Ready-made plywood, laminated veneer lumber and laminated lumber are treated in the same manner as for plate materials. Veneer is treated at a pressure of 10 to 25 kgf / cm depending on the species of wood. 2 The treatment is carried out for 30 to 120 minutes at a pressure of 10 ...
[0054] Next, the step of drying and curing the wood and wood material injected with the flame retardant is carried out through a step of drying, curing and stabilizing for a certain period of time at 50 to 70°C, preferably 60°C depending on the wood material, tree species, heartwood and thickness, and a step of curing the phenolic resin in the flame retardant at 100 to 150°C. For example, the board material is dry cured at 60°C for 24 to 28 hours and cured at 105°C for 24 hours to produce a flame retardant-treated wood. For example, the veneer is thin, so it is dry cured at 60°C for 12 to 24 hours and cured at 105°C for 6 to 12 hours to produce a flame retardant-treated veneer. For example, the particles and fibers are dried at 60°C for 12 to 24 hours and then cured at 105°C for 30 minutes to 2 hours.
[0055] Of the dried and hardened wood and wood materials, the wood and boards may be used as they are after the above-mentioned treatment, but the boards as well as veneers, particles, and fibers may be subjected to the next step, a heat-pressing process, to produce the final wood material.
[0056] The treated boards are used to make laminated timber or structural cross-laminated timber (CLT), and resorcinol adhesives or phenol-resorcinol co-condensation adhesives may be used. The treated veneer is then used to make plywood and laminated veneer lumber (LVL) using an adhesive. The treated particles or fibres are used to make particleboard or fibreboard through a normal hot pressing process using an adhesive. For example, 10% melamine resin (53% solids) and 3% 20% NH4Cl solution as a hardener are added to the flame retardant treated particles, which are then formed into a mat and then heated in a hot press at 175°C at 45-30-20kg / cm. 2 The heat and pressure process is then carried out for 7 minutes and 30 seconds (2-3.3-2 minutes) to produce a flame-retardant particleboard.
[0057] The flame retardant composition for wood and wood-based materials, and the method for producing flame-retardant wood and flame-retardant wood-based materials according to the present invention improve flame retardant performance while reducing the burden on the environment, thereby improving the inherent physical properties of wood and wood-based materials and preserving the natural patterns and aesthetics of wood, and therefore can be applied to wooden houses, wooden furniture, wooden cultural properties, and various household items.
[0058] The present invention will be described in detail below with reference to examples. It will be apparent to those skilled in the art that the following examples are merely illustrative for explaining the present invention in more detail, and the present invention is not limited to these examples. EXAMPLES
[0059] Flame retardant board treatment A radiata pine board (100 mm x 100 mm x 40 mm, longitudinal sealing) was placed in a pressure injector filled with a wood flame retardant composition, and subjected to pre-exhaust (0.08 MPa) at 43°C for 30 minutes and pressure of 20 kg / cm. 2 The pressure was increased by 1000 bar for 1 hour, followed by 30 minutes of post-exhaust (0.08MPa) for a reduced pressure and pressurization treatment. The flame retardant used was one in which the solid content of phenolic resin was 20.8wt%, the solid content of boric acid was 15.3wt%, the solid content of sodium borate was 19.2wt%, and the total solid content of boric acid-sodium borate was 34.5wt%, meaning that the solid content of boric acid-sodium borate was 1.66 times higher than the solid content of the phenolic resin.
[0060] The boards impregnated through the above fireproofing treatment were dried and cured at 60°C for 24 hours and then cured at 105°C for 24 hours to produce fire-retardant wood. The results of the fire resistance test of the fire-retardant treated boards using a cone calorimeter are as follows.
[0061] The weight gain rate (WPG: Weight Percent Gain) was 48.28%, the ignition time was 100 seconds, and the weight loss rate was 8.24%. Performance tests were conducted using a cone calorimeter in accordance with KS F ISO 5660-1, and the material met the flame retardant grade as shown in Figure 6 ((a): Total Heat Release Rate (THR), (b): Heat Release Rate (HRR)).
[0062] Physical properties (flame retardant board material / untreated board material) are density 0.60 / 0.42g / cm 2The moisture content was 8.81 / 7.83%. Furthermore, while the weight gain rate of the flame retardant-treated board was 48.28%, the results of the leaching treatment test (KS M 1701-2018) showed a weight loss rate of 28.12 ± 0.026%, confirming the effect of increasing the amount of flame retardant remaining in the sample and extremely high leaching resistance. Figure 2 shows photographs comparing untreated boards and flame retardant-treated boards before and after the leaching test. After 10 leaching treatments, the untreated board (right side of 1.) had severe cracks on the surface of the wood, while the flame retardant-treated board (right side of 2.) had a clean surface condition similar to before treatment, and had very high dimensional stability. EXAMPLES
[0063] Manufacturing of laminated lumber after fire retardant treatment of radiata pine boards Radiata pine boards (100 mm x 100 mm x 40 mm, longitudinally sealed) were placed in a pressure injector filled with a wood flame retardant composition and then subjected to a pressure of 14 kg / cm at 60°C. 2 The pressure treatment was carried out for 2 hours at a pressure of 10 ... 2 , 150℃, 10kgf / cm 2 The mixture was then hot pressed using a pressure cooker (35 min.).
[0064] The results of fire resistance tests using a cone calorimeter on fire-retardant treated radiata pine laminated timber are as follows:
[0065] The ignition time was no ignition, and the weight loss rate (600 seconds) was 7.16%. Performance tests were conducted using a cone calorimeter in accordance with KS F ISO 5660-1, and the result showed that the material satisfied the semi-inflammable grade, as shown in Figure 7 ((a): total heat release rate (THR), (b): heat release rate (HRR)).
[0066] The physical properties (fire-retardant laminated lumber / untreated laminated lumber) are density 0.60 / 0.42g / cm 2 , the moisture content was 8.81 / 7.83%. EXAMPLES
[0067] Production of plywood after veneer flame retardant treatment A larch veneer (2.4 mm thick) is placed in a pressurized injector filled with a wood flame retardant and is then heated to 14 kg / cm at 60°C. 2 The liquid flame retardant used had a composition in which the solid content of phenolic resin was 20.8 wt%, the solid content of boric acid was 15.3 wt%, and the solid content of sodium borate was 19.22 wt%, resulting in a total solid content of boric acid-sodium borate of 34.5 wt%. The veneer that had been injected through the above fireproofing treatment was dried and cured at 60°C for 24 hours and then hardened at 105°C for 24 hours. Five plywood sheets (with a coating amount of phenolic resin of 200 g / m2) that had been flame-retarded in this way were then cut into pieces and dried. 2 , 150℃, 10kgf / cm 2 The results of the fire resistance and physical property tests using a cone calorimeter for the plywood made from the flame retardant treated veneer are as follows:
[0068] The weight gain rate (WPG) was 30.09%, the ignition time was 99 seconds, and the weight loss rate (300 seconds) was 13.28%. Performance tests were conducted using a cone calorimeter in accordance with KS F ISO 5660-1, and the flame retardant grade was met as shown in Figure 8 ((a): total heat release rate (THR), (b): heat release rate (HRR)).
[0069] Physical properties (fire-retardant plywood / untreated plywood) are density 0.75±0.11 / 0.67±0.04g / cm 2 , moisture content was 9.05±0.04 / 9.53±0.07%, and tensile shear adhesive strength was 0.89±0.12 / 1.19±0.26N / mm 2 The water resistant tensile strength is 0.82 / 0.84N / mm 2 Therefore, the density of the plywood increases due to the flame retardant treatment, and there is no decrease in adhesive strength due to the flame retardant treatment, but in contrast, the treated material consisting only of a mixture of boric acid and sodium borate immediately peeled off at the adhesive site when cut, showing a large difference from the flame retardant consisting of the disclosed compound of phenolic resin, boric acid, and sodium borate. EXAMPLES
[0070] Flame retardant treatment of prefabricated plywood Prefabricated plywood (larch: 2.4 mm thick, 13-ply plywood, dimensions (T) 30 × (W) 100 × (L) 300 mm, radiata pine: 2.4 mm thick, 9-ply plywood, dimensions (T) 21 × (W) 100 × (L) 300 mm) and flame retardant were placed in a pressurizer and compressed at 14 kg / cm at 60°C. 2 The pressure treatment was carried out for 2 hours at a pressure of 1000 psi. The flame retardant used was a water-resistant flame retardant for wood, in which the ratio of the solid content of boric acid-sodium borate to the solid content of phenolic resin was 1.66, i.e., the solid content of phenolic resin was 20.8 wt%, the solid content of boric acid was 15.3 wt%, and the solid content of sodium borate was 19.2 wt%, resulting in a total solid content of boric acid-sodium borate of 34.5 wt%.
[0071] The board material impregnated through the fireproofing treatment was dried and cured at 60° C. for 24 hours and then cured at 105° C. for 24 hours to produce fire-retardant treated wood.
[0072] The results of fire resistance tests using a cone calorimeter on fire retardant treated radiata pine plywood are as follows:
[0073] The ignition time was 140 seconds, and the weight loss rate (at 300 seconds) was 9.2%. Performance tests were conducted using a cone calorimeter in accordance with KS F ISO 5660-1, and the flame retardant grade was met, as shown in Figure 9 ((a): total heat release rate (THR), (b): heat release rate (HRR)).
[0074] Physical properties (fire-retardant plywood / untreated plywood) are density 0.69 / 0.51g / cm 2 The moisture content was 7.70 / 7.44%. The weight gain (WPG) due to the fireproofing agent was 36.3%.
[0075] The results of the fire resistance test of the flame-retardant treated larch plywood using a cone calorimeter were as follows:
[0076] The ignition time was 187 seconds, and the weight loss rate (at 300 seconds) was 7.94%. Performance tests were conducted using a cone calorimeter in accordance with KS F ISO 5660-1, and the flame retardant grade was met, as shown in Figure 10 ((a): total heat release rate (THR), (b): heat release rate (HRR)).
[0077] Physical properties (fire-retardant plywood / untreated plywood) are density 0.75±0.03 / 0.67±0.08g / cm 2 , moisture content was 9.05±0.12 / 9.53±0.10%, tensile shear adhesive strength was 1.98±0.37 / 2.09N / mm 2 The water resistant tensile strength is 0.82±0.078 / 0.84N / mm 2 Therefore, it is clear that the density of the plywood increases due to the flame retardant treatment, and that the adhesive strength does not decrease due to the flame retardant treatment. In addition, while the weight increase rate of the flame retardant treated plywood due to the fireproofing treatment was 22.46±0.49%, the weight loss rate in the leaching test was only 7.2±0.27%, which shows that a large amount of flame retardant remains in the sample, resulting in extremely high resistance to leaching. EXAMPLES
[0078] Manufacture of fire-retardant particle board The flame retardant used was a flame retardant with a phenolic resin solid content of 20.8wt%, boric acid solid content of 15.3wt%, sodium borate solid content of 19.2wt%, and total solid content of boric acid-sodium borate of 34.5wt%, which is 1.66 times higher than the solid content of phenolic resin. Such flame retardants were mixed and treated in a coating machine so that the total dry particles were 30% and 50%, and then dried at 60°C for 24 hours and then treated at 150°C for 30 minutes to harden. To such particles, 10% melamine resin (solid content 53%) and 3% 20% NH4Cl solution as a hardener were added to the total dry weight of the particles, and after forming a mat, the mixture was heated at 175°C in a hot press at 45-30-20kg / cm. 2 The flame-retardant particleboard was manufactured by hot pressing under the conditions of pressure of 1000 and heat pressing for 7 minutes 30 seconds (2-3.3-2 minutes). The results of the fire resistance test of the 30% flame-retardant treated particleboard using a cone calorimeter are as follows.
[0079] The ignition time was 42 seconds, and the weight loss rate (at 300 seconds) was 13.42%. Performance tests were conducted using a cone calorimeter in accordance with KS F ISO 5660-1, and the flame retardant grade was met, as shown in Figure 11 ((a): total heat release rate (THR), (b): heat release rate (HRR)).
[0080] The results of the fire resistance test using a cone calorimeter for 50% flame retardant treated particleboard are as follows:
[0081] The ignition time was no ignition at all, and the weight loss rate (600 seconds) was 24.39%. Performance tests were conducted using a cone calorimeter in accordance with KS F ISO 5660-1, and the result showed that the material satisfied the quasi-noncombustible flare criteria, as shown in Figure 12 ((a): total heat release rate (THR), (b): heat release rate (HRR)).
[0082] The physical properties (30wt% flame retardant particle board / 50wt% flame retardant particle board / untreated particle board) are density 0.92±0.05 / 1.01±0.07 / 0.81±0.06g / cm 2 , moisture content 6.733±0.19 / 7.267±0.64 / 6.81±0.42%, bending strength 21.894±1.89 / 23.605±1.76 / 22.783±0.70N / mm 2 , and the wet bending strength was 7.01±0.67 / 7.56±0.81 / 6.53±0.97N / mm 2 , peel strength is 0.81±0.05 / 0.904±0.07 / 0.97±0.09N / mm 2 It was.
[0083] Yalinkilic, MK et al. (1998) reported that particleboard treated with boric acid and borax (4.7% treatment) had a 42.4% lower internal adhesive strength than untreated particleboard. The peel strength of particleboard treated with only boric acid and sodium borate solution (40% of the particle weight) was 0.27 N / mm 2 0.97N / mm for untreated particle board 2In contrast, when treated with the flame retardant consisting of phenol-boric acid-sodium borate disclosed in this disclosure, there was no statistical difference compared to the untreated one, even when the treatment was performed at 30% or 50% of the total dry weight of the particles (F = 1.826). In addition, it was found that the wet bending strength rather increased as the treatment amount increased compared to the untreated one, and the bending strength when wet was higher than that of the untreated one. In addition, as a result of the leaching treatment test (KS M 1701-2018) of the particleboard treated with the flame retardant consisting of the compound of phenol resin-boric acid-sodium borate disclosed in this disclosure, the weight loss rate (WPL: Weight percent) of (30% flame retardant particleboard / 50% flame retardant particleboard) was 1.01%. Loss) was 10.16±0.03% / 15.26±0.05%, and compared to the weight gain rate, the amount of flame retardant remaining in the particleboard was large, indicating high resistance to leaching. In addition, the leaching test results for the untreated particleboard shown on the right side of 1 in Figure 3 showed a thickness swelling rate of 48±0.8%, which indicates a large thickness expansion, whereas the particleboard treated with 50% flame retardancy (right side of 2) showed a thickness swelling rate of 12±0.3%, indicating very high dimensional stability. Therefore, in the treatment with the flame retardant consisting of the phenolic resin-boric acid-sodium borate compound of the present disclosure, the boric acid-sodium borate is trapped or sealed in the wood by the phenolic resin, which compensates for the defects of the reduced adhesive strength and vulnerability to water caused by boron, and helps to stabilize dimensions, and can compensate for the defect of the reduced internal bonding strength caused by the flame retardant treatment consisting of boric acid-sodium borate alone. EXAMPLES
[0084] Flame retardant treatment of larch veneer using a flame retardant consisting of a mixture of phenol-resorcinol resin, boric acid and sodium borate (PRB: Phenol-Resorcinol resin·Boron complex) 94g (1 mole) of phenol, 171.4g (2.0 moles) of 35% formalin, and 15g of water were placed in a resin reactor, and the pH was adjusted to 11 with NaOH. The reaction was carried out at 70°C for 1 hour to produce a liquid resol-type phenolic resin (solid content 51.7%, pH 11.0, viscosity 24.3cps). A boric acid-sodium borate solution was prepared by adding 25.53wt% of boric acid and 31.91wt% of sodium borate (borax), and the temperature was raised to 90°C to 100°C to produce a mixture of boric acid-sodium borate that dissolves well in water until it becomes transparent. The temperature was maintained at 60°C, and the mixture was reacted with the phenolic resin produced above for 2 hours to produce a mixture of 23.4wt% of phenolic resin, 14.03wt% of boric acid, and 14.03wt% of sodium borate. The solid content of the phenol resin was 21.3wt% and the solid content of the resorcinol resin was 9.1wt%, so that the total solid content of the resin was 30.4wt%, the solid content of the boric acid (Boric acid) was 12.8wt% and the solid content of the sodium borate (Sodium borate) was 15.9wt%, so that the total solid content of the boric acid-sodium borate was 31.57%. Subsequently, while maintaining the temperature at 60°C, 10g of resorcinol was added thereto, and the mixture was stirred for 15 minutes to dissolve, and then reacted for another 2 hours to produce a water-resistant phenol resorcinol-boric acid-sodium borate-based flame retardant for wood (pH 7.35, viscosity 36.9cps) with a phenol resin solid content of 21.3wt% and a resorcinol resin solid content of 9.1wt%, so that the total solid content of the resin was 30.4wt%, the boric acid solid content of 12.8wt%, and the sodium borate solid content of 15.9wt%, so that the total solid content of the boric acid-sodium borate was 28.7%.
[0085] A larch veneer (2.4 mm thick) is placed in a pressure injector filled with the above-mentioned wood flame retardant and is then heated to 25 kg / cm at 40°C. 2 The veneer that had been impregnated through the fireproofing treatment was then dry cured at 60°C for 24 hours and cured at 105°C for 24 hours. Five plywood sheets (with a phenolic resin coating of 200g / m2) made of fireproof veneer were then 2 , 150℃, 10kgf / cm 2The fire resistance and physical properties of the plywood made from the flame-retardant treated veneer were tested using a cone calorimeter, and the results are as follows:
[0086] The ignition time was 131 seconds, and the weight loss rate (at 300 seconds) was 14.28%. Performance tests were conducted using a cone calorimeter in accordance with KS FISO 5660-1, and the flame retardant grade was met as shown in Figure 13 ((a): total heat release rate (THR), (b): heat release rate (HRR)).
[0087] Physical properties (fire-retardant treated plywood / untreated plywood) are density 0.70±0.05 / 0.67±0.04g / cm 2 The moisture content was 7.70±0.06 / 9.53±0.07%. The weight gain (WPG) due to the fireproofing agent was 33.18±0.01%. The tensile shear adhesive strength was 0.99±0.08 / 1.19±0.26N / mm 2 It was. EXAMPLES
[0088] Flame retardant treatment of larch veneer using a flame retardant made of resorcinol-phenol resin·boron complex (RPB) 94g (1 mole) of phenol, 171.4g (2.0 moles) of 35% formalin, and 15g of water were placed in a resin reactor, and the pH was adjusted to 11 with NaOH. The reaction was carried out at 70°C for 1 hour to produce a liquid resol-type phenolic resin (solid content 51.7%, pH 11.0, viscosity 24.3cps). A boric acid-sodium borate solution was prepared by adding 25.53wt% of boric acid and 31.91wt% of sodium borate (borax), and the mixture was heated to 90°C to 100°C to produce a mixture of boric acid-sodium borate that was highly soluble in water until it became transparent. The mixture was then reacted with the phenolic resin produced above while maintaining the temperature at 60°C to produce a mixture of boric acid-sodium borate that was highly soluble in water, with a solid content of 23.4wt%, boric acid solid content of 14.03wt%, and sodium borate (Sodium The mixture was reacted for 2 hours until the solid content of boric acid-sodium borate was 17.54 wt%, and the total solid content of boric acid-sodium borate was 31.57%. Subsequently, 30 g of resorcinol was added while maintaining the temperature at 60°C, and the mixture was stirred for 15 minutes to dissolve, and then reacted for another 2 hours to produce a water-resistant flame-retardant adhesive for wood. The composition of the resorcinol-phenol co-condensed resin as the flame-retardant adhesive thus produced was such that the solid content of the phenol resin was 18.6 wt%, the solid content of the resorcinol resin was 28.6 wt%, the total solid content of the adhesive was 47.2 wt%, the solid content of boric acid was 9.1 wt%, the solid content of sodium borate was 11.4 wt%, the total solid content of boric acid-sodium borate was 20.5 wt%, and the remainder was distilled water 32.3 wt%. Such a flame-retardant adhesive hardens to form a fire-resistant layer, imparting flame retardancy, and the flame-retardant components in the adhesive diffuse into the adjacent wood material, i.e., veneer or board, imparting flame retardancy. The pH of the flame-retardant adhesive made of resorcinol-phenol co-condensation resin / boric acid / sodium borate complex (RPB) thus produced was 7.62 and the viscosity was 48.3 cps. A flame-retardant adhesive prepared in a weight ratio of 100 parts flame-retardant adhesive: 15 parts wheat flour: 30 parts hardener was applied to a radiata pine veneer board having a thickness of 2.4 mm at a coating amount of 200 g / m2. 2The heat and pressure conditions for the plywood were 10 kgf / cm 2 The adhesive was applied to the surface of the plywood at 150°C for 20 minutes. A flame-retardant adhesive consisting of resorcinol-phenol co-condensation resin, boric acid and sodium borate complex (RPB) was applied at a rate of 300 g / m2. 2 The coating was applied at 40°C, dried at 25-30°C for 24 hours, and then cured at 150°C for 30 minutes.
[0089] The fire resistance of the manufactured plywood was tested using a cone calorimeter in accordance with KS F ISO 5660-1, and the results showed that it satisfied the flame retardant grade, as shown in Figure 14 ((a): total heat release rate (THR), (b): heat release rate (HRR)).
[0090] The physical properties of the manufactured plywood (fire-retardant plywood / untreated plywood) are density 0.65±0.01 / 0.43±0.03g / cm 2 The moisture content is 4.7±0.15 / 4.8±0.20%, and the density is increased by injecting flame retardant. The tensile shear adhesive strength in the non-waterproof state is 1.10±0.26 / 1.18±0.30N / mm 2 The results of the t-test (t=0.34) showed that there was no statistically significant difference in the non-waterproof tensile shear adhesive strength between the two groups.
[0091] Water-resistant tensile shear adhesive strength: 0.99±0.09 / 0.98±0.09N / mm 2 The results of the t-test (t=0.07) showed that there was no statistically significant difference between the water-resistant tensile shear adhesive strength of both groups. Therefore, when flame-retardant plywood is manufactured using flame-retardant adhesives, good plywood is obtained without any decrease in adhesive strength due to the flame retardant, and the results of the test using a cone calorimeter in accordance with KS F ISO 5660-1 satisfy the flame-retardant grade.
[0092] The flame-retardant treated wood and wood materials produced in Examples 1 to 7 were subjected to performance tests using a cone calorimeter in accordance with KS F ISO 5660-1, and all of them met the flame retardant grade standard or higher, as shown in Figures 6 to 14. Here, the flame retardant grade is a grade that has a heat release rate of 200 kW / m2 when measured for 5 minutes with 50 kW heat during cone calorimeter measurement. 2 Less than or equal to 8MJ / m of total heat emission 2 The semi-non-combustible grade is one that meets the conditions above, and has a heat release rate of 200kw / m2 when measured for 10 minutes against 50kW heat. 2 Less than or equal to 8MJ / m of total heat emission 2 It satisfies the following conditions.
[0093] Fig. 4 shows the surface condition of untreated wood and wood treated with flame retardant according to the embodiment of the present invention as a result of an ignition test using a cone calorimeter. The wood treated with flame retardant according to the embodiment of the present invention has a charred layer formed on the surface due to high temperature, but the back side is in a clean state, and it can be seen that the thickness of the charred layer is significantly reduced compared to untreated board material.
[0094] In the present invention, as described above, the flame retardancy is doubled and the solid content of the high concentration boric acid-sodium borate mixture is stably used, so that a stable flame retardant is produced by using phenolic resin as a carrier to contain it, which plays a role in improving the decrease in adhesive strength and the moisture-sensitive nature caused by the inorganic treatment of boric acid-sodium borate, and a flame retardant agent having affinity for adhesion is produced from such a boric acid-sodium borate mixture and a stable phenolic resin compound, thereby producing flame retardant wood and fire retardant wood materials that maintain the natural pattern and clean surface of wood, are not easily leached by water, and have dimensional safety. Therefore, it is expected that wood, which is called canned carbon dioxide, can be used for a long period of time in buildings, and will greatly contribute to the prevention of global warming and carbon neutrality measures.
[0095] As described above, in the present specification and drawings, specific terms are disclosed to describe specific embodiments of the present invention. However, these terms are used in a general sense to facilitate understanding of the present invention and are not intended to limit the scope of the present invention. These terms will be apparent to those skilled in the art to which the present invention pertains. [Industrial Applicability]
[0096] According to an embodiment of the present invention, it is possible to provide wood having excellent flame retardancy. Therefore, the flame retardant wood according to an embodiment of the present invention is particularly suitable as a material for various building materials such as architectural wall materials, ceiling materials, floor materials, bathroom wood, doors, as well as furniture, bedding, interior decoration, and the like.
Claims
1. A flame retardant composition for wood and wood-based materials, comprising boric acid, sodium borate, and a water-soluble phenolic resin.
2. The flame retardant composition for wood and wood-based materials according to claim 1, comprising 16 to 36 wt% of the phenolic resin, 8 to 18 wt% of the boric acid, 10 to 22 wt% of the sodium borate, and 18 to 40 wt% of boric acid-sodium borate.
3. The flame retardant composition for wood and wood-based materials according to claim 1, wherein the phenolic resin is a liquid resol type prepared by adding phenol, formalin, and water to a resin reactor and adjusting the pH to 10.7 to 11.0 with sodium hydroxide (NaOH).
4. The phenolic resin is a liquid resol type prepared by adding the phenol and the formalin in a molar ratio of phenol:formalin=1:1.63 to 2.4 to the resin reactor, adjusting the pH to 10.7 to 11.0 with sodium hydroxide (NaOH), and reacting at 70° C. to 80° C. The flame retardant composition for wood and wood-based materials according to claim 3,
5. The flame retardant composition for wood and wood-based materials according to claim 1, further comprising resorcinol or bisphenol, the resorcinol or bisphenol being a liquid resol type capable of producing a co-condensation resin with phenol.
6. 6. The flame retardant composition for wood and wood-based materials according to claim 5, wherein the flame retardant composition contains resorcinol in an amount of 10 to 40 wt %.
7. 7. The flame retardant composition according to claim 6, wherein the resorcinol is 23-33 wt %, the phenolic resin is 15-21 wt %, the resorcinol-phenolic resin is 38-54 wt %, the boric acid is 6.8-10.9 wt %, the sodium borate is 8.5-13.7 wt %, and the boric acid-sodium borate is 15.3-24.6 wt %.
8. 3. The flame retardant composition for wood and woody materials according to claim 1 or 2, characterized in that the boric acid and sodium borate are mixed to prepare a boric acid-sodium borate mixture, and the boric acid-sodium borate mixture is prepared by adding 25.53 wt % of boric acid and 31.91 wt % of sodium borate to water as a boric acid-sodium borate solution, heating the solution to 90°C to 100°C, preparing a transparent boric acid-sodium borate mixture that is highly soluble in water, and mixing the mixture with a phenolic resin to cause a reaction.
9. S1) Preparing wood or wood-based material; S2) preparing a wood flame retardant consisting of a mixture of phenolic resin and boric acid-sodium borate; S3) injecting the wood flame retardant comprising the phenolic resin-boric acid-sodium borate compound obtained in step S2) into the wood or wood-based material; and S4) drying and hardening the impregnated wood or wood-based material; A method for producing flame-retardant wood or a flame-retardant wood material, comprising:
10. The step S2) S2-1) mixing boric acid and sodium borate in a solvent to produce a boric acid-sodium borate mixture; and S2-2) mixing and reacting the mixture of boric acid and sodium borate with a phenolic resin; A method for producing the flame-retardant wood or wood material according to claim 9, comprising:
11. The method for producing a flame-retardant wood or wood-based material according to claim 9, further comprising the step of: S5) subjecting the wood or wood-based material to a heat-pressing process to produce a final wood-based material.
12. 10. The method for producing a flame-retardant wood or wood material according to claim 9, wherein the wood or wood material is a veneer, board, particle, strand, or fiber obtained from a log, or a plywood, laminated veneer lumber (LVL), laminated lumber, cross-laminated timber (CLT), particle board, strand board, or fiberboard made from the same.
13. The method for producing a flame-retardant wood or wood-based material according to claim 10, further comprising a step of producing a phenolic resin prior to step S2-2, wherein the step of producing the phenolic resin comprises adding phenol, formalin and water to a resin reactor, adjusting the pH to 10.7 to 11.0 with sodium hydroxide (NaOH) and reacting the resin to obtain a liquid resol type.
14. 11. The method for producing a flame-retardant wood or wood-based material according to claim 10, characterized in that in step S2-1), boric acid and sodium borate are added to water, the temperature is raised to 90°C to 100°C, and a mixture of boric acid and sodium borate that dissolves well in water until it becomes transparent is produced, and then in step S2-2), the produced phenolic resin is mixed with 16 to 36 wt% phenolic resin, 8 to 18 wt% boric acid, 10 to 22 wt% sodium borate, and 18 to 40 wt% boric acid-boric acid, and reacted.
15. 10. The method for producing a flame-retardant wood or wood-based material according to claim 9, characterized in that in step S2), a compound of phenolic resin, boric acid and sodium borate is produced, and then resorcinol is added to the compound of phenolic resin, boric acid and sodium borate to produce a flame retardant for wood.
16. The method for producing a flame-retardant wood or a flame-retardant wood material according to claim 15, wherein the flame retardant for wood is comprised of 23-33 wt% resorcinol and 15-21 wt% phenolic resin, with a resorcinol-phenolic resin content of 38-54 wt%, 6.8-10.9 wt% boric acid and 8.5-13.7 wt% sodium borate, with a boric acid-sodium borate content of 15.3-24.6 wt%.
17. 10. The method for producing a flame-retardant wood or wood material according to claim 9, wherein in step S3), the injection method is diffusion and penetration at normal pressure.
18. In the step S3), the injection method is a pressurization and depressurization method, and the main pressure is 10 to 25 kg / cm 2 10. The method for producing a flame-retardant wood or wood material according to claim 9, characterized in that the treatment is carried out at a temperature of from 0.5 to 120 minutes.
19. 19. The method for producing a flame-retardant wood or wood material according to claim 18, characterized in that in step S3), before and after the main pressurization, pre-exhaust is performed for 30 minutes and post-exhaust is performed for 10 to 30 minutes.
20. The method for producing a flame-retardant wood or wood material according to claim 9, further comprising a step of stabilizing the wood or wood material injected in step S4) at room temperature, drying the wood or wood material at 50 to 70°C for a certain period of time, and then curing the resin at 100 to 150°C.
21. 12. The method for producing a flame-retardant wood or wood-based material according to claim 11, wherein in step S5), the veneer is produced as plywood or laminated veneer lumber (LVL), the board is produced as laminated lumber or cross-laminated timber (CLT), the particles are produced as particle board, the strands are produced as strand board, and the fibers are produced as fiberboard.
22. A flame-retardant wood produced by the method according to any one of claims 9 to 21.
23. A flame-retardant wood material produced by the method according to any one of claims 9 to 21.
Citation Information
Patent Citations
Wood modifier and preparation method thereof
CN104118022A
Preparation of modified wood
JP1989299006A
Manufacture of modified wood
JP1990008002A
wooden fire door
JP1994056465U
Laminated lumber
JP1995214517A